Individual Knowledge on Institutional Capability of the Regional Legislative Council in the Formation of Regional Legal Products in Bolaang Mongondow Selatan Regency - Hastuti, Evi (KnE Social Sciences, 2025)
The formation of local legal products is a legislative function that is the responsibility of the Regional Legislative Council (DPRD). The issue of institutional capacity to the quality and level of knowledge of DPRD members in the formation of local regulations has often been a concern. This study aims to determine individual knowledge on the institutional capability of the DPRD in the formation of regional legal products in Bolaang Mongondow Selatan Regency. This research uses a qualitative descriptive method. The informants of this research are the head of legislation, leaders of the DPRD, Bapemperda, and the head of the legal section of the regional secretariat. Data collection methods included observation, interviews, and secondary data. The results showed that the majority of DPRD members do not have a background in law or legislation. Many come from various professions (entrepreneurs, activists, politicians), so their technical mastery of academic drafting, legal drafting techniques, and regulation harmonization is limited. Only a small number of DPRD members understand how to draft legal products that meet formal and substantive requirements. DPRD members play a more significant role in providing political direction or determining the substance of policies in outline, rather than in drafting normative details. The harmonization process is rarely understood by DPRD members. Harmonization is usually the task of the executive’s legal department or expert consultants. There are capacity-building programs as training, workshops, and expert assistance that are routinely provided to DPRD members. However, these programs have a significant impact on the quality of individual knowledge of DPRD members.